THE PRINCIPLE OF IMMEDIACY IN ABBREVIATED CRIMINAL PROCEDURE ACCORDING TO THE 2011 CRIMINAL PROCEDURE CODE OF SERBIA (Part Two: Personal and Temporal Aspects of Immediacy): (Part Two: Personal and Temporal Aspects of Immediacy) - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper focuses on the personal and temporal aspects of the principle of immediacy in summary proceedings under the Serbian Criminal Procedure Code of 2011. There are two exceptions to the rule of irreplaceability of judges in general proceedings, which are also applied mutatis mutandis in the summary procedural form. Article 507, paragraph 3 of the CPC is the only special provision related to the personal judicial aspect of immediacy, reserved exclusively for summary proceedings, aimed at strengthening their efficiency. In summary proceedings, there are two specific deviations from the rule of mandatory presence of the accused at the main trial, while the remaining two are possible based on the analogous application of general procedural provisions. The trial of an absent and fugitive accused is not contrary to Article 33, paragraph 4 of the Constitution of the Republic of Serbia, nor to international legal documents. Unlike general criminal proceedings, where the presence of the authorized prosecutor at the main trial is unconditionally required, in summary proceedings, there is one justified exception to this rule for reasons of procedural expediency. The temporal aspect of the principle of immediacy is better protected in the summary procedural form. This is evidenced by the legal guideline that the main trial in summary proceedings should be completed without interruption whenever possible, as well as the inability to extend the legal deadlines for pronouncing, announcing, and drafting the judgment in writing. The author concludes that the greatest limitation of the principle of immediacy in summary proceedings is related to the personal party aspect, while its strongest support lies in its temporal aspect. This ensures that this principle in summary proceedings balances, in a specific way, between the demand for its realization and the need for its limitation, in order to promote the idea of efficiency.